Case report: Therapy adherence, MTTP variants, and course of atheroma in two patients with HoFH on low-dose, long-term lomitapide therapy - Kayikcioglu, Meral; Ozkan, Hasan Selcuk; Yagmur, Burcu; Bayraktaroglu, Selen; Vardarli, Asli Tetik (Frontiers in Genetics, 2023)
Background: Homozygous familial hypercholesterolemia (HoFH) is a rare and devastating genetic condition characterized by extremely elevated levels of low-density lipoprotein cholesterol (LDL-C) leading to an increased risk of premature atherosclerosis. Patients with Homozygous familial hypercholesterolemia mostly present with mutations in LDLR; however, herein, we present two cases with concomitant microsomal triglyceride transfer protein mutations, who showed different clinical courses and treatment adherence on long-term therapy with the new MTTP inhibitor lomitapide. Objectives: We aimed to present the possibility of preventing the progression of atherosclerotic burden with effective and safe LDL-C reduction in patients with Homozygous familial hypercholesterolemia on low-dose lomitapide therapy and emphasize the role of treatment adherence in therapy success. Methods: We present two patients with phenotypically Homozygous familial hypercholesterolemia, a compound heterozygous woman and a simple homozygous man, both with LDLR and additional MTTP mutations, who were treated with the MTTP-inhibiting agent lomitapide, with different treatment compliances. The role of impulsivity was investigated through Barratt Impulsivity Scale 11, and the extent of the atherosclerotic burden was followed up using coronary artery calcium scoring, echocardiographic and sonographic findings, and, eventually, through a strict follow-up of laboratory parameters. The patients were on lomitapide for 8 and 5 years, respectively, with no adverse effects. Conclusion: When accompanied by good adherence to therapy, low-dose lomitapide on top of standard lipid-lowering therapy with decreased frequency of lipid apheresis prevented the progression of atherosclerotic burden. Non-compliance might occur due to patient impulsivity and non-adherence to a low-fat diet.